High resolution MALDI-TOF-MS and MS/MS: Application for the structural characterization of sulfated oligosaccharides. Issue 5 (October 2019) - Lesur, David; Duhirwe, Gilbert; Kovensky, José
Sulfated oligosaccharides are involved in important biological events that are often modulated by specific sequences and sulfation patterns, but their structural analysis remains challenging. Matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) analysis of three different sulfated oligosaccharides (Fondaparinux, the octasulfated pentasaccharide, a disulfated heparin-derived tetrasaccharide1, and an octasulfated maltoheptaose)2 was performed using the 2-(4-hydroxyphenylazo)benzoic acid-tetramethylguanidinium (HABA-TMG2 ) matrix. High resolution mass spectrometry of the main ions observed was successful, and this was complemented by tandem mass spectrometry (MS/MS) analysis for structural assessment. Despite sulfate losses, fully sulfated molecular ions were observed and these allowed the determination of oligosaccharide structures: UA-GlcNAc-UA(2S)-AnhMan(6S) for compound1 and (Glc6S)6 -Glc (1S, 6S) for compound2 .